A Semantic Analysis of Speech Style Used by Barrack Obama - Ratnawati Ratnawati; Rosmiaty Rosmiaty; Hermin Lutfiah Mita Pratiwi (Tamaddun Life, 2021)
This research aimed to find out the types of speech style Obama used and the dominant type he used. This research is a qualitative research with a descriptive design. In analyzing the data, the writer read the transcript in the video and analyzed the data based on Martin Joos theory. In this research, the writer found that there were three speech styles used by Barrack Obama they were formal style, casual style and intimate style which is formal style has 13 data representing 59%, casual style has 9 data representing 36% and the last is intimate style found only in 1 data or representing 5% of all data. Based on the results there were some conclusions first. There were twenty two sentences to be analyzed and obtained three of speech style they were formal, casual and intimate styles and the dominant style that often appears is the formal style because of the situation in the speech is formal.